2011
DOI: 10.1007/s00203-011-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Colistin A and colistin B among inhibitory substances of Paenibacillus polymyxa JB05-01-1

Abstract: Recently, we isolated and reported the antagonism of Paenibacillus polymyxa JB05-01-1 (P. polymyxa JB05-01-1) against Gram-negative bacteria. Here, we provide more insights and attribute the abovementioned antagonism to the production of colistins A and B, which were purified by Amberlite column exchange, C18 column hydrophobicity, superdex 75 16/60 gel filtration chromatography connected to fast protein liquid chromatography and identified by MALDI TOF/TOF, and manual nanospray analysis. The amount of colisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous reports have shown that the anti-fungal mechanism of action of Paenibacillus sp. involves production of potent antifungal compounds including polymyxins, fusaricidins, colistins, volatiles, and lytic enzymes (He et al, 2007 ; Raza et al, 2008 , 2009 , 2015 ; Naghmouchi et al, 2012 ). In particular, Paenibacillus is well-known to combat F. graminearum by employing fusaricidin, a compound named after Fusarium as noted earlier (Kajimura and Kaneda, 1996 , 1997 ; Beatty and Jensen, 2002 ; Choi et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the anti-fungal mechanism of action of Paenibacillus sp. involves production of potent antifungal compounds including polymyxins, fusaricidins, colistins, volatiles, and lytic enzymes (He et al, 2007 ; Raza et al, 2008 , 2009 , 2015 ; Naghmouchi et al, 2012 ). In particular, Paenibacillus is well-known to combat F. graminearum by employing fusaricidin, a compound named after Fusarium as noted earlier (Kajimura and Kaneda, 1996 , 1997 ; Beatty and Jensen, 2002 ; Choi et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main roles of P. polymyxa are to stimulate plant growth through the production of various plant hormones and to promote immunity of the rhizosphere . In addition, P. polymyxa strains are also known to produce several antibiotics and hydrolytic enzymes, including polymyxins, fusaricidins, colistin, proteases, β ‐1,3‐glucanases, cellulases, xylanase, chitinases, and so on, which play important roles in the biocontrol of plant pathogens . P. polymyxa E681 was isolated from the rhizosphere of winter barley grown in South Korea .…”
Section: Introductionmentioning
confidence: 99%
“…Auxin, cytokinin, indole‐3‐acetic acid (IAA) and other indolic compounds referring to simulating plant growth were found in P. polymyxa culture (Lebuhn et al , ; Timmusk et al , ; Phi et al , ). P. polymyxa strains are also known to produce several antibiotics and hydrolytic enzymes, including polymyxins, fusaricidins, colistin, proteases, β ‐1,3‐glucanases, cellulases, xylanase, chitinases and so on, which play important roles in the biocontrol of plant pathogens (Parry et al , ; Beatty & Jensen, ; He et al , ; Li & Jensen, ; Raza et al , ; Ariza et al , ; Naghmouchi et al , ). Some strains of P. polymyxa were capable to colonise host root tips and form robust biofilms (Timmusk et al , ) as well as change plant defence‐related gene expression (Timmusk & Wagner, ).…”
Section: Introductionmentioning
confidence: 99%